Inactivation of the nucleus accumbens core or medial shell attenuates reinstatement of sugar-seeking behavior following sugar priming or exposure to food-associated cues. - Peagan Lin; Wayne E Pratt (PLoS ONE, 2014)
Re-exposure to either palatable food or to conditioned stimuli associated with food is known to reinstate food-seeking after periods of abstinence. The nucleus accumbens core and shell are important for reinstatement in both food- and drug-seeking paradigms, although their potential differential roles have been difficult to delineate due to methodological differences in paradigms across laboratories. The present studies assessed the effects of temporary inactivation of the core or shell on priming- and cue-induced reinstatement of food-seeking in identically-trained rats. Inactivation of either the nucleus accumbens core (Experiment 1A; N = 10) or medial shell (Experiment 1B; N = 12) blocked priming-induced reinstatement in an equivalent manner. Similarly, inactivation of the core or medial shell (Experiments 2A & 2B; N = 11 each) also blocked cue-induced reinstatement, although there was also a significant treatment day X brain region X drug order interaction. Specifically, rats with core inactivation reinstated lever-pressing on the vehicle injection day regardless of whether that was their first or second test, whereas rats that had medial shell inactivation on the first day did not significantly reinstate lever-pressing on the second day of testing (when they received vehicle). Yohimbine, while a reportedly robust pharmacological stressor, was ineffective at inducing reinstatement in the current stress-induced reinstatement procedure. These data suggest that both the nucleus accumbens core and shell serve important roles in reinstatement of food-seeking in response to priming and cues.